Enterovirus D68 and Panton-Valentine Leukocidin–Positive Staphylococcus Aureus Respiratory Coinfection with Fatal Outcome. (January 2016) - Ravishankar, Sanjita; Chapin, Kimberle; Alexander-Scott, Nicole; Wills, Hale; Merritt, Christopher; Jacobson, Melanie; Kleris, Renee; Alhinai, Zaid; Sediva, Ivona; Muratore, Christopher; Mermel, Leonard; Mangray, Shamlal
A previously healthy 10-year-old girl with a 2-day history of upper respiratory illness and fever rapidly developed respiratory failure and sepsis with leukopenia, and expired despite attempts at resuscitation. Postmortem examination revealed bilateral necrotizing pneumonia and evidence of disseminated intravascular coagulation. Nasopharyngeal swabs and lung tissue submitted to the Centers for Disease Control and Prevention (CDC) were positive for Enterovirus D68 (EV-D68). Blood and lung cultures were positive for methicillin-resistant Staphylococcus aureus (MRSA). The isolates were submitted to the CDC and were found to be positive for the toxin Panton-Valentine leukocidin. We describe a fatality related to invasive toxin-mediated MRSA associated with EV-D68 coinfection, along with the clinical, laboratory, and autopsy findings, which provided important clues, prompting further investigation at the CDC to arrive at the correct diagnosis.